Pengembangan Kemampuan Berfikir Induktif Melalui Analisis Data Statistik - Zuhriyah, Aqilatuz; Ernasari, Ernasari; Handoko, Sri; Mahardika, I Ketut; Safuro, Vina Riski; Prasetyo, Agung Adi (Jurnal Ilmiah Wahana Pendidikan, 2024)
Abstract Received: Revised: Accepted: Statistics has a very important role in physics especially in understanding and analyzing experimental data and in explaining physical phenomena involving many particles or complex systems. Some of the basics of statistics in physics include descriptive statistics, probability distributions, inferential statistics, Boltzmann distribution and Maxwell-Boltzmann distribution, quantum statistics, statistical theory, Monte Carlo methods, and weakness theory. Statistics is an important tool in physics for processing and analyzing experimental data, modeling the behavior of physical systems, and making predictions based on probability. This helps physicists understand the complex world of physics and contributes to the development of better physical theories. (*)